Preparation method of two-dimensional nano carbon material and two-dimensional nano carbon material
By using potassium iodide as an activator, the biomass powder is mixed with the potassium iodide solution, and after freeze-drying and pyrolysis treatment, two-dimensional nanocarbon materials with high specific surface area and degree of graphitization are prepared, which solves the problems of complex preparation process, high cost and safety hazards in the prior art, and achieves efficient and environmentally friendly production results.
Patent Information
- Application Number
- CN202411673095.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-28
AI Technical Summary
The preparation process of existing two-dimensional nanocarbon materials is complex, has high cost, and the chemicals used are toxic and corrosive, with safety hazards and equipment corrosion problems, making it difficult to achieve large-scale production.
Potassium iodide is used as the activator, and the pulverized biomass powder is fully mixed with the potassium iodide solution, and lyophilized is lyophilized to form a two-dimensional nanocarbon material. This method is non-toxic and mild at high temperatures, has little corrosiveness to the equipment, and potassium iodide can be recycled to reduce production costs.
It realizes efficient preparation of two-dimensional nanocarbon materials, has a high specific surface area and a degree of graphitization, and is suitable for supercapacitors, photocatalysis and metal catalyst carriers, and at the same time reduces production costs and environmental risks, making it suitable for large-scale production.
Smart Images

Figure CN119528120A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of biochar production, and in particular to a method for preparing a two-dimensional nanocarbon material. Background Art
[0002] Due to its unique two-dimensional sheet structure advantages, including large specific surface area, good electron diffusion channels, and easily regulated active sites, two-dimensional nanocarbon materials are gaining more and more attention and favor in the fields of supercapacitors, catalysts, and adsorption. my country is a large agricultural and forestry country. Agricultural and forestry wastes are widely available, low in cost, and high in carbon content. They are good precursors for the preparation of carbon materials. Therefore, the preparation of two-dimensional nanocarbon materials using agricultural and forestry wastes has important research significance and broad application prospects.
[0003] However, two-dimensional nanocarbon materials also have the disadvantages of complex preparation and high cost. In particular, in the traditional preparation process, the most widely used chemicals are toxic and highly corrosive zinc chloride and potassium hydroxide. Corrosive metal salts and strong acid washing materials such as hydrochloric acid are also required during processing. In this process, there are not only safety hazards but also great corrosion to equipment, which is not conducive to large-scale production. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a method for preparing a two-dimensional nanocarbon material.
[0005] According to a first aspect of an embodiment of the present invention, a method for preparing a two-dimensional nanocarbon material comprises the following steps:
[0006] S1. Add the crushed biomass powder into the potassium iodide solution and mix thoroughly to obtain a first mixture.
[0007] Specifically, the biomass is first washed with water to clean the dust on the surface of the biomass, then dried in an oven at low temperature, crushed with a pulverizer, and 80-120 mesh biomass powder is screened out as a biomass raw material for standby use; at the same time, a potassium iodide solution is prepared, and the premixed biomass raw material is added to the prepared potassium iodide solution, and fully stirred for 12 hours, and fully stirred in an oil bath for 12 hours, so that the biomass and potassium iodide are fully mixed.
[0008] S2. freeze-drying the first mixture and grinding it into powder to obtain a second mixture.
[0009] Specifically, after the biomass and the mixed solution are fully stirred, they are placed in a freeze dryer for freeze drying for 24 hours. After the freeze drying is completed, a solid mixture is obtained, which is ground into powder.
[0010] S3. Pyrolyzing the second mixture under an inert gas atmosphere to obtain a third mixture.
[0011] Specifically, the second mixture is placed in a porcelain boat and transferred to a quartz tube, and a certain flow of inert gas is continuously introduced to exhaust the air in the quartz tube. The quartz tube is placed in a pyrolysis furnace, and a certain flow of nitrogen is continuously introduced during the pyrolysis process at a rate of 50 ml / min.
[0012] The pyrolysis furnace is heated at a pyrolysis rate of 10°C / min, the target temperature range is 400°C-800°C, and the total pyrolysis time is 1 hour after reaching the target temperature. The quartz tube is taken out of the pyrolysis furnace and cooled to room temperature in air, thereby obtaining a third mixture in the quartz tube.
[0013] S4. Wash the third mixture with deionized water and dry it to obtain a biomass-based two-dimensional nanocarbon material.
[0014] Specifically, after the pyrolysis furnace is cooled to room temperature, the carbon material is taken out from the quartz tube and washed with deionized water until it is neutral, and then dried to obtain a two-dimensional sheet-like nano-carbon material.
[0015] In this process, the present invention uses a single potassium iodide as an activator, which is safe, green and has low corrosion to equipment. When the biomass and potassium iodide are evenly mixed and frozen, water condenses into ice to form an ice template, and the salt crystals are pushed by the frozen ice interface and accumulate on the ice surface, squeezing the biomass at the same time. After drying, the ice sublimates during the freeze-drying process, thereby forming a salt support structure that wraps the biomass powder. During the pyrolysis process, when the temperature of the reaction system is higher than the melting point of potassium iodide, the salt crystals melt into a molten liquid, providing a liquid reaction medium for the pyrolysis of the biomass. Potassium iodide has the characteristics of rapid heat transfer, which can promote the diffusion of reactants and make the reaction of biochar more sufficient.
[0016] Potassium iodide crystals serve as a template for two-dimensional carbon materials and play a structural guiding role. The biomass adheres closely to the surface of the potassium iodide template and undergoes a pyrolysis reaction. After the pyrolysis reaction is completed and cooled to room temperature, the liquid salt is converted into crystals, which can be removed by dissolving in deionized water. After drying, the desired two-dimensional nanocarbon material is obtained.
[0017] Furthermore, the potassium iodide separated by water washing can be recycled after drying, thereby reducing production costs and avoiding potential environmental risks.
[0018] A two-dimensional carbon material according to the second aspect of an embodiment of the present invention is a two-dimensional carbon material prepared by any of the above-mentioned preparation methods. Specifically, the two-dimensional nanocarbon material prepared by the above-mentioned preparation method has a very high specific surface area and degree of graphitization, which is conducive to use in supercapacitor electrode materials, photocatalysis, metal catalyst carriers, etc.
[0019] Beneficial effects:
[0020] The invention is simple to operate and adopts a single potassium iodide as an activator. It is not only non-toxic and mild at high temperature and has little corrosion to equipment, but also the potassium iodide separated by washing with water can be recycled again after drying. The production cost is low, secondary pollution is not easy to cause, and it is conducive to industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0022] Figure 1 is a transmission electron microscope image of the two-dimensional nanocarbon material of Example 1 of the present invention;
[0023] Figure 2 is a scanning electron microscope image of the two-dimensional nanocarbon material of Example 2 of the present invention;
[0024] Figure 3 is a Raman spectrum of the two-dimensional nanocarbon material of Example 4 of the present invention;
[0025] Figure 4 It is a transmission electron microscope image of the carbon material prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0026] Embodiments of the present invention are described in detail below, and the embodiments described with reference to the accompanying drawings are exemplary.
[0027] Example 1
[0028] In this embodiment, four different types of biomass were selected and crushed, and 1g of birch, bamboo, wheat straw, and plastic were weighed for standby use, and two-dimensional nanocarbon materials were prepared according to the following preparation method;
[0029] Step 1: Wash the biomass with water, clean the dust on the surface of the biomass, dry it in an oven at low temperature, crush it with a pulverizer, and select 80-120 mesh biomass powder as biomass raw material for standby use.
[0030] Step 2: Place 4 g of potassium iodide in a beaker, add 50 ml of deionized water, wait until the solid is completely dissolved, add 1 g of biomass powder, put in a rotor, and stir in an oil bath for 12 h;
[0031] Step 3: Place the mixed solution into a freeze dryer and freeze dry for 24 hours. After freeze drying, a white solid mixture is obtained, which is ground into powder;
[0032] Step 4: Place the mixture in a porcelain boat, transfer it to a quartz tube, and continue to introduce a certain flow of inert gas to exhaust the air in the tube. Then, during the pyrolysis process, maintain a certain flow of nitrogen gas continuously at a rate of 50 ml / min.
[0033] Step 5: Place the quartz tube in a pyrolysis furnace. Raise the temperature of the pyrolysis furnace to 800°C at a pyrolysis rate of 10°C / min and maintain for 1 hour. When the pyrolysis furnace cools to room temperature, remove the quartz tube from the pyrolysis furnace; remove the carbon material, wash it with deionized water until it is neutral, and dry it to obtain a two-dimensional sheet-like nanocarbon material.
[0034] Biochar prepared from different biomass raw materials was collected and tested. The physical properties of the prepared carbon materials are shown in Table 1:
[0035] Table 1 Physical properties of two-dimensional nanocarbon materials prepared from different biomass
[0036] Serial number Biomass Specific surface area (m2 / g) <![CDATA[I D / I G ]]> 1 birch 1513 1.108 2 bamboo 1476 1.119 3 Wheat straw 1439 1.113 4 plastic 1380 1.237
[0037] It can be seen from the above table that the two-dimensional carbon material prepared from birch has a larger specific surface area and a higher degree of graphitization.
[0038] Example 2
[0039] In this embodiment, the effects of different molten salts on the properties of two-dimensional nanocarbon materials were tested, and only the type of molten salt was changed, wherein the molten salt was potassium iodide, potassium bromide, and potassium chloride, and the two-dimensional nanocarbon material was prepared according to the following preparation method;
[0040] Step 1: Wash the birch sawdust with water, clean the dust on the surface of the birch sawdust, dry it in an oven at low temperature, crush it with a pulverizer, and select 80-120 mesh birch powder as a biomass raw material for later use.
[0041] Step 2: Place 4 g of molten salt in a beaker, add 50 ml of deionized water, wait until the solid is completely dissolved, add 1 g of birch powder, put in a rotor, and stir in an oil bath for 12 h;
[0042] Step 3: Place the mixed solution into a freeze dryer and freeze dry for 24 hours. After freeze drying, a white solid mixture is obtained, which is ground into powder;
[0043] Step 4: Place the mixture in a porcelain boat, transfer it to a quartz tube, and continue to introduce a certain flow of inert gas to exhaust the air in the tube. Then, during the pyrolysis process, maintain a certain flow of nitrogen gas continuously at a rate of 50 ml / min.
[0044] Step 5: Place the quartz tube in a pyrolysis furnace. Raise the temperature of the pyrolysis furnace to 800°C at a pyrolysis rate of 10°C / min and maintain for 1 hour. When the pyrolysis furnace cools to room temperature, remove the quartz tube from the pyrolysis furnace; remove the carbon material, wash it with deionized water until it is neutral, and dry it to obtain a two-dimensional sheet-like nanocarbon material.
[0045] Biochar prepared from different molten salts was collected and tested. The physical properties of the prepared carbon materials are shown in Table 2:
[0046] Table 2 Physical properties of two-dimensional nanocarbon materials prepared by different molten salts
[0047]
[0048] It can be seen from the above table that the specific surface area and ID / IG value of the two-dimensional nanocarbon materials prepared by using different types of molten salts are different, especially when the molten salt is potassium iodide, the specific surface area is the highest and the ID / IG value is the smallest.
[0049] Example 3
[0050] In this embodiment, the effect of the ratio of potassium iodide on the properties of the two-dimensional nanocarbon material was tested, other factors were kept unchanged, only the ratio of biomass to potassium iodide was changed, and the two-dimensional nanocarbon material was prepared according to the following preparation method;
[0051] Step 1: Wash the birch sawdust with water, clean the dust on the surface of the birch sawdust, dry it in an oven at low temperature, crush it with a pulverizer, and select 80-120 mesh birch powder as a biomass raw material for later use.
[0052] Step 2: Place 1g, 2g, 3g, 4g, and 5g of potassium iodide in a beaker, add 50ml of deionized water, and wait until the solid is completely dissolved. Then, add 1g of birch powder, place a rotor, and stir in an oil bath for 12h.
[0053] Step 3: Place the mixed solution into a freeze dryer and freeze dry for 24 hours. After freeze drying, a white solid mixture is obtained, which is ground into powder;
[0054] Step 4: Place the mixture in a porcelain boat, transfer it to a quartz tube, and continue to introduce a certain flow of inert gas to exhaust the air in the tube. Then, during the pyrolysis process, maintain a certain flow of nitrogen gas continuously at a rate of 50 ml / min.
[0055] Step 5: Place the quartz tube in a pyrolysis furnace. Raise the temperature of the pyrolysis furnace to 800°C at a pyrolysis rate of 10°C / min and maintain for 1 hour. When the pyrolysis furnace cools to room temperature, remove the quartz tube from the pyrolysis furnace; remove the carbon material, wash it with deionized water until it is neutral, and dry it to obtain a two-dimensional sheet-like nanocarbon material.
[0056] The biochar prepared by different molten salts was collected and tested. The physical properties of the prepared carbon materials under different ratios of birch powder and potassium iodide are shown in Table 3:
[0057] Table 3 Physical properties of two-dimensional nanocarbon materials prepared with different potassium iodide ratios
[0058] Serial number Biomass to potassium iodide ratio Specific surface area (m2 / g) 1 1:0.5 533 2 1:2 709 3 1:4 1513 4 1:6 1327 5 1:8 1286 6 1:10 1062
[0059] From the table above, we can see that when the ratio of birch powder to potassium iodide is different, the specific surface area and ID / IG value of the prepared two-dimensional nanocarbon material are different. When the ratio of corn stalk to potassium iodide is 1:4, the specific surface area of the prepared material is the largest. As the proportion of potassium iodide increases, the activation effect introduces defects, resulting in an increase in the ID / IG value.
[0060] Among them, ID / IG is the intensity ratio of the D band to the G band in the Raman spectrum, which describes the degree of graphitization of the carbon material. From the above test results, it can be seen that the carbon material prepared with potassium iodide as the molten salt has the highest degree of graphitization. Compared with potassium bromide and potassium chloride, potassium iodide has a stronger carbon layer exfoliation effect, can catalyze the occurrence of various reactions, and is helpful to improve the degree of graphitization of carbon materials and promote the formation of graphene-like structures.
[0061] Example 4
[0062] In this embodiment, the influence of different pyrolysis temperatures on the properties of the two-dimensional nanocarbon material is tested, other factors are kept unchanged, only the pyrolysis temperature is changed, and the two-dimensional nanocarbon material is prepared according to the following preparation method;
[0063] Step 1: Wash the birch sawdust with water, clean the dust on the surface of the birch sawdust, dry it in an oven at low temperature, crush it with a pulverizer, and select 80-120 mesh birch powder as a biomass raw material for later use.
[0064] Step 2: Place 4 g of potassium iodide in a beaker, add 50 ml of deionized water, wait until the solid is completely dissolved, add 1 g of birch powder, place a rotor, and stir in an oil bath for 12 h;
[0065] Step 3: Place the mixed solution into a freeze dryer and freeze dry for 24 hours. After freeze drying, a white solid mixture is obtained, which is ground into powder;
[0066] Step 4: Place the mixture in a porcelain boat, transfer it to a quartz tube, and continue to introduce a certain flow of inert gas to exhaust the air in the tube. Then, during the pyrolysis process, maintain a certain flow of nitrogen gas continuously at a rate of 50 ml / min.
[0067] Step 5: Place the quartz tube in a pyrolysis furnace. Raise the temperature of the pyrolysis furnace at a pyrolysis rate of 10°C / min to 400°C, 500°C, 600°C, 700°C, and 800°C, respectively, and maintain for 1 hour. When the pyrolysis furnace cools to room temperature, remove the quartz tube from the pyrolysis furnace; remove the carbon material, wash it with deionized water until it is neutral, and dry it to obtain a two-dimensional sheet-like nanocarbon material.
[0068] The two-dimensional nanocarbon materials prepared at different pyrolysis temperatures were collected and tested. The physical properties of the carbon materials prepared under different pyrolysis temperature conditions are shown in Table 4:
[0069] Table 4 Physical properties of two-dimensional nanocarbon materials prepared at different pyrolysis temperatures
[0070] Serial number Pyrolysis temperature Specific surface area (m2 / g) ID / IG 1 400 790 1.368 2 600 1104 1.214 3 800 1513 1.108 4 1000 1052 1.083
[0071] As can be seen from the table above, the pyrolysis temperature has a great influence on the specific surface area of carbon materials. As the temperature increases, the specific surface area first increases and then decreases. At 800°C, the specific surface area is the largest. At 900°C and 1000°C, due to the high temperature, part of the carbon structure collapses and the specific surface area decreases.
[0072] Among them, at a pyrolysis temperature of 800°C, it has the highest specific surface area, up to 1513m2 / g, because the molten salt plays the role of template and activator in the pyrolysis process. On the one hand, the molten salt is converted into liquid at a temperature higher than the melting point. In the liquid phase, the molten salt can diffuse into the carbon skeleton and inhibit the stacking of carbon layers, which is conducive to the formation of a two-dimensional sheet structure; on the other hand, potassium ions undergo an oxidation-reduction reaction with carbon to produce an etching effect to form a porous structure, and the escape of pyrolysis gas products is also conducive to the pore formation of carbon materials, thereby forming a rich pore structure and microporous structure.
[0073] Comparative Example 1
[0074] In this embodiment, the effect of carbonate ratio on the properties of two-dimensional nanocarbon materials, wherein the carbonate here is potassium bicarbonate, and the two-dimensional nanocarbon material is prepared according to the following preparation method;
[0075] Step 1: Wash the birch sawdust with water, clean the dust on the surface of the birch sawdust, dry it in an oven at low temperature, crush it with a pulverizer, and select 80-120 mesh birch powder as a biomass raw material for later use.
[0076] Step 2: Place 0.5 g, 1 g, 2 g, 3 g, and 4 g of carbonate and 4 g of potassium chloride in a beaker, add 50 ml of deionized water, wait until the solid is completely dissolved, add 1 g of birch powder, put in a rotor, and stir in an oil bath for 12 h;
[0077] Step 3: Place the mixed solution into a freeze dryer and freeze dry for 24 hours. After freeze drying, a white solid mixture is obtained, which is ground into powder;
[0078] Step 4: Place the mixture in a porcelain boat, transfer it to a quartz tube, and continue to introduce a certain flow of inert gas to exhaust the air in the tube. Then, during the pyrolysis process, maintain a certain flow of nitrogen gas continuously at a rate of 50 ml / min.
[0079] Step 5: Place the quartz tube in a pyrolysis furnace. Raise the temperature of the pyrolysis furnace to 800°C at a pyrolysis rate of 10°C / min and maintain for 1 hour. When the pyrolysis furnace cools to room temperature, remove the quartz tube from the pyrolysis furnace; remove the carbon material, wash it with deionized water until it is neutral, and dry it to obtain a two-dimensional sheet-like nanocarbon material.
[0080] The biochar prepared under different potassium bicarbonate ratios was collected and tested. The specific surface area of the prepared carbon material is shown in Table 5:
[0081] Table 5 Specific surface area of nanocarbon materials prepared under potassium bicarbonate ratio conditions
[0082] Serial number Biomass: Potassium Bicarbonate: Potassium Chloride Specific surface area (m2 / g) 1 1:0:4 965 2 1:0.5:4 1183 3 1:1:4 1269 4 1:2:4 1436 5 1:3:4 1765 6 1:4:4 1618
[0083] It can be seen from the above table that potassium bicarbonate does promote the increase in the specific surface area of nanocarbon materials, and when the ratio of biomass: potassium bicarbonate: potassium chloride reaches 1:3:4, the specific surface area of the two-dimensional nanocarbon material reaches its peak.
[0084] Comparative Example 2
[0085] In this embodiment, the effect of only carbonate on the properties of the two-dimensional nanocarbon material is tested, wherein the carbonate here is potassium bicarbonate, and the two-dimensional nanocarbon material is prepared according to the following preparation method;
[0086] Step 1: Wash the birch sawdust with water, clean the dust on the surface of the birch sawdust, dry it in an oven at low temperature, crush it with a pulverizer, and select 80-120 mesh birch powder as a biomass raw material for later use.
[0087] Step 2: Place 0.5 g, 1 g, 2 g, 3 g and 4 g of carbonate in a beaker, add 50 ml of deionized water, wait until the solid is completely dissolved, add 1 g of birch powder, put in a rotor, and stir in an oil bath for 12 h;
[0088] Step 3: Place the mixed solution into a freeze dryer and freeze dry for 24 hours. After freeze drying, a white solid mixture is obtained, which is ground into powder;
[0089] Step 4: Place the mixture in a porcelain boat, transfer it to a quartz tube, and continue to introduce a certain flow of inert gas to exhaust the air in the tube. Then, during the pyrolysis process, maintain a certain flow of nitrogen gas continuously at a rate of 50 ml / min.
[0090] Step 5: Place the quartz tube in a pyrolysis furnace. Raise the temperature of the pyrolysis furnace to 800°C at a pyrolysis rate of 10°C / min and maintain for 1 hour. When the pyrolysis furnace cools to room temperature, remove the quartz tube from the pyrolysis furnace; remove the carbon material, wash it with deionized water until it is neutral, and dry it to obtain a two-dimensional sheet-like nanocarbon material.
[0091] The prepared biochar was collected and tested with a nitrogen adsorption-desorption instrument. The specific surface area of the prepared carbon material is shown in Table 6, and the transmission electron microscopy image of the carbon material is shown in Figure 4 .
[0092] Table 6 Specific surface area of nanocarbon materials prepared under potassium bicarbonate only condition
[0093] Serial number Biomass: Potassium Bicarbonate Specific surface area (m2 / g) 1 1:0.5 866 2 1:1 992 3 1:2 1152 4 1:3 1508 5 1:4 1367
[0094] It can be seen from the above table that potassium bicarbonate has a promoting effect on the increase of the specific surface area of carbon materials, but through Figure 4 It can also be seen that the carbon produced under the condition of only potassium bicarbonate is a conventional honeycomb cluster structure, which is different from the carbon produced in the embodiment of the present invention. Figure 1 The two-dimensional sheet structure shown in is significantly different.
[0095] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example.
[0096] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A method for preparing a two-dimensional nanocarbon material, characterized in that: The method comprises the following steps: S1, adding the crushed biomass into a potassium iodide solution, mixing evenly, freeze-drying, and grinding into powder to obtain biomass powder; S2. Pyrolyzing the biomass powder under an inert gas atmosphere, washing and drying the powder to obtain a biomass-based two-dimensional nanocarbon material.
2. The method for preparing a two-dimensional nanocarbon material according to claim 1, characterized in that: The biomass is any one of birch, bamboo, wheat straw and plastic, or a combination of at least two of them.
3. The method for preparing a two-dimensional nanocarbon material according to claim 1, characterized in that: The mass ratio of the biomass to potassium iodide is in the range of 1:0.5 to 1:
10.
4. The method for preparing a two-dimensional nanocarbon material according to claim 1, characterized in that: The mass ratio of the biomass to potassium iodide is in the range of 1:1 to 1:
5.
5. The method for preparing a two-dimensional nanocarbon material according to claim 1, characterized in that: The temperature range of pyrolysis of the biomass powder in an inert gas atmosphere is 400° C.-1000° C.
6. The method for preparing a two-dimensional nanocarbon material according to claim 1, characterized in that: The temperature range of pyrolysis of the biomass powder in an inert gas atmosphere is 600° C.-800° C.
7. The method for preparing a two-dimensional nanocarbon material according to claim 6, characterized in that: The pyrolysis temperature was increased at a pyrolysis rate of 10°C / min.
8. A two-dimensional nanocarbon material, characterized in that: A two-dimensional nanocarbon material prepared by the method for preparing a two-dimensional nanocarbon material according to any one of claims 1 to 7.